As boas novas pela palavra impressa: impressos e imprensa protestante no Brasil (1837-1930) - Vasconcelos, Micheline Reinaux de (2010)
This work deals with the Protestant press in Brazil, covering the Baptist and Presbyterian s printed production, between the year 1837 and 1930. Firstly, we introduce the Protestant press production, namely, the multiplicity of ways in which it manifested itself, and the interests which it tried to serve. Following this, we tackle its diffusion, which includes the printing centers, and the ways of distribution used by editors. The perusal of these sources demonstrates that they were engaged in the struggle for the Brazilian religious spaces, but also as a doctrinal teaching tool for those converted to Protestantism. Being present since the early Protestant missionaries undertakings in the country, the circulation of those printed texts starts with the beginning of systematic distribution of Bibles and leaflets by the Bible Societies foreign institutions in Brazil. This is therefore, the initial milestone of our study. The final line is the year 1930, because in the following years the nature of relationship between the Brazilian political and religious fields was changed, mainly due to the fact that the National State and the Catholic Church became closer again. Finally, the studying of such press circulation warrants proposing that the Protestant printed papers and press were so deeply related to the building of Protestantism in the Brazilian territory, that we can therefore assure that the establishment of this press was a constitutive piece of a Protestant culture in Brazil